Pemberdayaan Ekonomi Masyarakat Desa Tegalega - Joko Utomo; Markus Diantoro; Aripriharta Aripriharta; Nadea Catur Nurmayanti; Ade Siyanti Nurul Hidayah (Jurnal KARINOV, 2023)
Dillem Wilis Agroedutourism has only collaborated with several parties but not directly with the community. Therefore, based on the priority of the problems, it is necessary to innovate towards internet-based online information to increase the expansion of marketing information for Dillem Willis Trenggalek Agrotourism. The hope is that Dillem Wilis Agrotourism can be known by the wider community. With this website, it can provide insight to the people of Trenggalek and outside the city that the Dillem Wilis plantation in Trenggalek Regency has an agro-edutourism tourism destination based on dairy cows and coffee which is suitable for use as educational facilities, namely the Science Techno Park and the Agricultural Technology Park. The steps taken include maximizing the use of the website, expanding marketing information and providing information on sales of coffee and dairy products on the website to increase visitors and turnover. The result of this service is that Dillem Wilis members have editing and marketing skills for websites. Members of Dillem Wilis are also starting to be able to use the website as a marketing medium for selling coffee and milk. Consumers make purchases from a website page that is connected to Dillem Wilis' WhatsApp, members prepare orders, then send them to the consumer's address. This strategy is efficient in increasing marketing information to Dillem Wilis. Keywords— Agrotourism, Dillem wilis, Website, Training